Sequential surface and subsurface flow modeling in a tropical aquifer under different rainfall scenarios. (March 2022) - Jimenez, Mariana; Velásquez, Nicolás; Jimenez, Jhon Esteban; Barco, Janet; Blessent, Daniela; López-Sánchez, Jacqueline; Castrillón, Sebastián Córdoba; Valenzuela, Carlos; Therrien, René; Boico, Vinicius Ferreira; Múnera, Juan Camilo
Abstract: The La Miel River watershed is an area of high hydrological interest in Colombia due to its abundant water resources, high annual precipitation, and hydroelectric power generation. This work proposes a sequential modeling framework to quantify the spatially and temporally variable groundwater recharge and to analyze its impact on piezometric fluctuations in the study area, where the groundwater flow is affected by geological faults. Water Modeling Framework (WMF) and HydroGeoSphere (HGS) models have been used to calculate groundwater recharge and distribution of hydraulic heads, respectively. Recharge computed with WMF is used as input to HGS to compare groundwater flow 1) with uniform and spatially variable recharge, 2) with and without discrete fractures, and 3) during dry and wet conditions. The results generate valuable knowledge for water resource management and highlight the importance of groundwater recharge estimation and a proper representation of fractured aquifers. Highlights: Distributed hydrological simulations to calculate groundwater recharge. Comparison between uniform and spatio-temporally variable groundwater recharge. Influence of regional faults on groundwater flow.